1979
DOI: 10.1073/pnas.76.8.3632
|View full text |Cite
|
Sign up to set email alerts
|

A DNA primase specified by I-like plasmids.

Abstract: An enzyme has been isolated from Escberichia coli strains harboring the I-like plasmid R64drdll, which is capable of initiating DNA synthesis -on the circular, singlestranded DNA of phages 4X174, fd, and G4. In the conversion of these templates to duplex forms in vitro, the enzyme can substitute for the functions of E. coli dnaB-dnaC-dnaG proteins, E. coli RNA polymerase, and E. coli dnaG protein, respectively. The enzyme requires all four ribonucleoside triphosphates for optimal activity, although a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 31 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…Because of the biological parallel between F and the I-like conjugative plasmids, it also seems possible that the Tral protein has DNA primase activity. It has been concluded that F does not encode a DNA primase, since it did not suppress a chromosomal dnaG temperature-sensitive mutation (36), nor did extracts from cells containing the F-like plasmids Rldrd-16 or R100-1 provide DNA priming activity in an in vitro DNA replication system (21). However, the plasmid specificity of traI might have defeated either of these attempts to detect an F-like-plasmid-encoded DNA primase.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the biological parallel between F and the I-like conjugative plasmids, it also seems possible that the Tral protein has DNA primase activity. It has been concluded that F does not encode a DNA primase, since it did not suppress a chromosomal dnaG temperature-sensitive mutation (36), nor did extracts from cells containing the F-like plasmids Rldrd-16 or R100-1 provide DNA priming activity in an in vitro DNA replication system (21). However, the plasmid specificity of traI might have defeated either of these attempts to detect an F-like-plasmid-encoded DNA primase.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the primase protein is transferred in noncatalytic amounts, and in addition, at least an equal number of Sog-160 molecules is transferred. It is known that Incll plasmid primase protein purifies as a DNA-binding protein (21). Therefore a substantial fraction of the transferred single-stranded DNA may be complexed with Sog proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with the protein concentration of the extracts measured by the method of Lowry et al (32), these values served to calculate the gp␣ concentrations. DNA primase was assayed in vitro in the presence of rifampin in an extract of E. coli dnaB dnaC mutant strain BC1304 as described previously (28,29). Viral fd DNA was used as the template for the primase and complementary-strand synthesis.…”
Section: Resultsmentioning
confidence: 99%